Praktek Dan Pendampingan Penyusunan Laporan Keuangan Sederhana Untuk UMKM Di Kecamatan Ciampea Bogor - Damayanty, Prisila; Widjanarko, Widjanarko; Nurdiana, Diah; Djunaidy, Djunaidy; Istiqomah, Rulyannas Tasya; Fadilah, Khoirul; Aulia, Tazkia; Purba, Sekararum Sherlenadya (ASOSIASI IDEBAHASA KEPRI, 2025)
This activity aims to analyze the practical process and assistance in preparing simple financial reports for micro, small and medium enterprises (MSMEs) in Ciampea District, Bogor. The method used in this activity is a case study with a qualitative approach. Data was collected through in-depth interviews with MSME owners and financial managers as well as direct observation of the practice of preparing financial reports. The results show that practice and assistance in preparing simple financial reports provide significant benefits for MSMEs in improving their financial understanding and skills.